EFFECT OF AGE AND JOB DESIGNATION ON VISUAL DYSFUNCTION AMONG COMPUTER USERS AT THE NATIONAL OPEN UNIVERSITY OF NIGERIA. - Olubiyi, Simeon Kayode; Afolayan, Joel Adeleke; Okesina, Bidemi (West African Journal of Nursing, 2015)
Competitiveness in today's world requires the use of computers for problem solving. This often demands prolonged working hours with its attendant health hazards. The study was carried out to determine the frequency of existence of visual dysfunction arising from prolonged usage of computer among staff of NOUN. Specifically, this study looked into persistent computer visual dysfunctions among NOUN staff and also examined whether these visual problems were linked with age and job designation of staff. The study was a cross-sectional survey adopting multi-stage random sampling method in the 17 NOUN Study Centres. The sample size for the study was 297; this was determined by the minimum sample size calculation from a total population of 902 staff of NOUN as at the time of the survey. A self-administered and structured questionnaire was used to gather information for the study. Snellen's test was used to determine visual acuities of the respondents. Frequency, percentage and chi-square (p<0.05) were used to interpret, illustrate and establish strength of associations among the variables. The findings of the study revealed that majority of visual dysfunctions observed were among the 31 - 42 years age group who were mostly chronic computer users. Also, academic staff category whose roles are largely computer intensive were observed to have less desirable visual acuities compared to their counterparts. This study concludes that prolonged computer usage may trigger hypermetropia, allergic conjunctivitis; itching eyes and photophobia, as these were prominent among computer users at the NOUN. It was, however, suggested that sensitization programmes on safe and effective computer use among staff most especially academics should be encouraged by institutional authorities.